SISTEM INFORMASI INVENTORY BERBASIS WEBSITE PADA CV TRIO JAYA SENTOSA - Putra, Johan Robert; Manurung, Ria; Widiastuti, Rosalina Yani (Electro Luceat, 2024)
The Web-Based Inventory Information System at CV Trio Jaya Sentosa is a final project aimed at addressing the manual issues in Inventory management at a cigarette distribution company, which has an impact on work efficiency, speed, and accuracy in report generation. This research employs observation, interviews, and literature review as data collection methods. The development method used is the prototype method. This system is built as a web-based application using the CodeIgniter 3 framework, PHP programming language, and MySQL database. The web-based information system is designed to enable CV Trio Jaya Sentosa to manage transactions, employee data, and customer data. The system generates various types of real-time reports, including sales reports by person, sales reports, sales summaries, purchase reports, Inventory reports, goods retrieval reports, sales stock reports, and warehouse stock reports. During its development, the system involves user evaluation regarding functionality and user interface to meet the company's needs. Based on user evaluations, it is evident that this Inventory Information System can address manual issues, improve data processing accuracy and speed, and provide real-time information. A recommended using the system, it is to continually involve users in the maintenance and improvement processes to maintain performance and reliability